(untitled) (The Research of Medical Science Review, 2025)
Anemia is a common condition among patients admitted to the medical intensive care unit (ICU), and its prevalence may increase during the course of hospitalization. This study aims to evaluate the frequency of anemia in patients at the time of admission to the ICU and three days post-admission, to identify any significant changes and to explore potential contributing factors. The study found that the frequency of anemia was significantly higher after three days of ICU admission, highlighting the need for better monitoring and management of hemoglobin levels in critically ill patients.